A QGIS-based graphical user interface for application and evaluation of SWAT-MODFLOW models. (January 2019) - Park, Seonggyu; Nielsen, Anders; Bailey, Ryan T.; Trolle, Dennis; Bieger, Katrin
Abstract: This article presents QSWATMOD, a QGIS-based graphical user interface for application and evaluation of SWAT-MODFLOW models. QSWATMOD includes: (i) pre-processing modules to prepare input data for model execution, (ii) configuration modules for SWAT-MODFLOW options, and (iii) post-processing modules to view and interpret model results. QSWATMOD, written in Python, creates linkage files between SWAT and MODFLOW models, runs a simulation, and displays results within the open source Quantum Geographic Information System (QGIS) environment. QSWATMOD is equipped with functionalities that assist in storing and retrieving user and default configuration settings and parameter values, performing the linkage and simulation processes, and uses various geo-processing functionalities (e.g., selection, intersection, union) of QGIS. The use of QSWATMOD is demonstrated through an application to the 471 km 2 Middle Bosque River Watershed in central Texas. As the number of SWAT-MODFLOW users grows worldwide, QSWATMOD can be a valuable tool to assist in creating and managing SWAT-MODFLOW projects. Highlights: A new graphical user interface (QSWATMOD) is introduced to facilitate the linkage of SWAT and MODFLOW models. QSWATMOD is created as a QGIS plug-in tool, allowing maps of domains and variables to be viewed. QSWATMOD can link existing SWAT and MODFLOW models, or create a single-layer MODFLOW model. QSWAMOD runs SWAT-MODFLOW and displays model results using charts and maps. Model output can be compared with observed stream discharge and groundwater levels.